Multi-Dimensional Backward Stochastic Riccati Equations, and Applications - Michael Kohlmann; Shanjian Tang (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
Multi-dimensional backward stochastic Riccati differential equations (BSRDEs in short) are studied. A closed property for solutions of BSRDEs with respect to their coefficients is stated and is proved for general BSRDEs, which is used to obtain the existence of a global adapted solution to some BSRDEs. The global existence and uniqueness results are obtained for two classes of BSRDEs, whose generators contain a quadratic term of L (the second unknown component). More specifically, the two classes of BSRDEs are (for the regular case N > 0)
urn:nbn:de:bsz:352-opus-5791
Keywords: 330; Kontrolltheorie; Stochastischer Prozess; Theorie